Quantum of proof when case for the prosecution depends substantially or wholly on circumstantial evidence: irresistible conclusion test or reasonable beyond a doubt test? - Shair Mohamad, Mohd Akram (Routledge, 2011)
There seems to be apparent judicial conflict as to the quantum of evidence required when the case for the prosecution is based wholly or substantially on circumstantial evidence. The traditional preponderant view - is that to succeed, the prosecution must show that the circumstantial evidence must be irresistibly consistent with the guilt of the accused and inconsistent with his innocent - the so called irresistible conclusion test. The other view is that the usual test applies in a criminal case i.e. that the prosecution must prove his case beyond a reasonable doubt suffices. This apparent difference of judicial views is seen in Malaysia, Australia, New Zealand and India, all countries whose legal systems, rooted in history, is based on the common law adversarial system. The paper addresses this conflict, with a view to suggesting how such a conflict can be resolved. Some insights from the Islamic law position on circumstantial evidence are also examined with a view to resolving the lingering conflict of opinions among the common law jurisdictions.